Features and Visitor Impressions of the Riam Merasap Waterfall Tourist Spot in Pisak Village, Seventeen District, Bengkayang Regency - Yolandra, Utin Kenny; Oramahi, Hasan Ashari (Jurnal Biologi Tropis, 2024)
Bengkayang Regency has a bunch of cool tourist spots, and one standout is the Merasap Waterfall in Pisak Village, Seventeen District. To really understand how a tourist area is developing, we need solid and representative data, especially from those who have actually visited. This info should reflect the visitors' own experiences. That's why knowing how visitors perceive the place is super important for future development plans. This study looks into how the local community views the growth of the Merasap Waterfall area in Pisak Village, Seventeen District, and also dives into factors like population, education, jobs, and the socio-cultural vibe of the area. We used a survey method with a sampling technique based on the Slovin formula. Overall, visitors think the development of the Merasap Waterfall tourist area is pretty great, giving it a thumbs up for the progress made in Pisak Village, Seventeen District, Bengkayang Regency.